Hysteretic behaviour of bracing-type pure aluminium shear panels by experimental tests. - De Matteis, Gianfranco
This paper deals with experimental tests aimed at assessing the structural performance of pure aluminium shear panels to be employed as passive energy dissipation devices with a bracing type configuration. The AW1050 A H24 is adopted as the basic material. It is an aluminium alloy with negligible content of impurity, allowing it to be considered as a pure aluminium. In this paper, the results of four full-scale 5 mm thick multi-stiffened square-shaped specimens tested under cyclic diagonal loads and characterized by different slenderness ratios are presented. In order to determine the main resisting mechanisms for different shear strain demands, a careful examination of the experimental evidences is provided. Then, the global performance of tested shear panels is evaluated by the comparison of the obtained hysteretic responses, evidencing the effect of the plate slenderness on the energy dissipation capacity. Finally, a suitable analytical model, which could be useful to implement global dynamic non-linear analysis, is set up in order to interpret the behaviour of shear panels for which the development of premature buckling phenomena is completely inhibited.
Keywords: Pure aluminium; Shear panels; Supplemental damping; Dissipative devices; Passive control; Experimental analysis; Analytical models